Investigation and analysis of the demand for smart home automation in patients with ischemic stroke and functional impairment (脑梗死伴功能障碍患者对智慧居家模块需求的调查分析) - FEI Cailian (费才莲); XIE Juan (谢娟); ZHANG Jingyi (张静怡); WANG Yu (王瑜); GAO Liandi (高连娣) (Association of Integrative Nursing, 2023)
Objective To establish a comprehensive, scientific, and reasonable smart home automation system for patients with ischemic stroke and functional impairment by conducting a questionnaire survey on the requirements of a smart home automation system. Methods The researchers developed a questionnaire titled "Requirements of a smart home automation system for patients with ischemic stroke and functional impairment" to assess the specific needs of patients who suffered from ischemic stroke and were unable to live independently. A total of 100 patients participated in the survey. Results The results of the questionnaire survey involving 100 individuals revealed that only 43. 00%(43/100)of the respondents were familiar with intelligent home systems, and a mere 21. 00%(21/100)had previous experience with similar smart systems. When asked about their willingness to accept a smart home automation system that could be installed and customized to provide convenience in daily life, including monitoring vital signs and medication usage, as well as aiding in rehabilitation training, 46. 00%(46/100) of the participants expressed their willingness of acceptance. Further investigation revealed that complex operation, impractical function and expensive cost were main reasons behind the reluctance of the rest 54 individuals to accept the system. The respondents expressed the highest demand for the electronic medication box monitoring system, followed by the sleep monitoring system and the vital sign monitoring system. Conclusion The findings indicated that patients with ischemic stroke and functional impairment had limited awareness and acceptance of smart home automation system. In order to ensure that the implementation of this automation system provides tangible benefits to patients, it is crucial to enhance its functionality, actively promote awareness among the target population, and establish an effective foundation for subsequent clinical trials of the intelligent home management system software. (目的 调查脑梗死伴功能障碍患者对智慧居家管理模块的需求, 为进一步建立完善、科学、合理的智慧居家管理模块提供依据。方法 采用自拟"脑梗死伴功能障碍患者对智慧居家模块的需求"调查问卷, 选取2020年4月-2023年4月医院收治的100例脑梗死伴功能障碍中生活不能完全自理的患者进行调查。结果 43(43. 00%)例患者了解智慧居家系统, 但只有21(21. 00%)例患者使用过类似的智能系统。当被问及"有一个智慧居家管理系统, 可在现有居家电器、门、窗等基础上进行安装改造, 旨在为您解决居家不便、进行生命体征及服药监测、帮助您进行康复训练等, 是否愿意接受"时, 46(46. 00%)例患者表示愿意接受, 而不愿意接受的原因包括操作复杂、实用性低、价格昂贵。患者对智慧居家管理系统功能的需求程度排前三位的分别是电子药盒监测系统、睡眠监测系统和生命体征监测系统。结论 脑梗死伴功能障碍患者对于智慧居家模块的了解程度低、接受意愿较低; 应通过加强功能完善、积极宣传普及等措施, 为智慧居家管理系统软件后期投入临床试验提供有效基础, 确保智慧居家模块的实施能够给患者带来确切益处。)